A MORPHOPHONOLOGICAL ANALYSIS OF ENGLISH LOANWORD ADAPTATION IN INDONESIAN EFL SPEAKING CONTEXTS - Arsy Damopolii; Jhems Richard Hasan; Abdul Kadir Ismail; Marina Pakaja; Zulkifli Akhmad (English Education Department at FKIP Nommensen University, 2026)
This study investigates the morphophonological adaptation of English loanwords used by Indonesian EFL students during speaking activities. Employing a descriptive qualitative approach, the study involved 60 students from the English Education Department of IAIN Sultan Amai Gorontalo. Data were collected through audio and video recordings of classroom discussions, presentations, video assignments, and examinations. A total of 16 English loanwords were identified and analyzed through transcription, coding, and classification based on morphophonological categories by comparing the adapted forms with their original English counterparts. The analysis revealed nine major morphophonological processes, namely sound substitution, vowel simplification, syllabification, stress neutralization, consonant cluster simplification, epenthesis, sound omission, orthographic adaptation, and morphological integration. The findings indicate that vowel simplification, sound substitution, syllabification, and stress neutralization were the most recurrent processes, reflecting the strong influence of Indonesian phonological and morphological systems on the adaptation of English-derived vocabulary. The study demonstrates that English loanwords are systematically reconstructed to conform to Indonesian linguistic patterns during spoken communication. These findings contribute to morphophonological scholarship by providing empirical evidence of the interaction between phonological and morphological adaptation in EFL speaking contexts and offer pedagogical insights for improving pronunciation awareness in English language teaching.